The Occupations of Nurses & Midwives: Initial findings from the NMC-census data linkage project - Jamieson, Michelle; Atherton, Iain (International Journal of Population Data Science, 2026)
Background The nursing and midwifery workforce faces persistent shortages and increasing reliance on international recruitment. Retention and return to practice are therefore major policy priorities. However, professional registration does not necessarily indicate current clinical employment, and register data alone provide limited information on registrants’ occupational circumstances. Objectives To utilize the linked Nursing and Midwifery Council (NMC) register data to the 2021 Census of England and Wales to describe registrants’ employment status and occupations at the time of the census and examine variation by profession and geography. Data sources and participants Comprehensive NMC register data from 2018, 2021, 2022 and 2023 linked to the full 2021 Census of England and Wales. The study population includes registered nurses, nursing associates and midwives. Methods Census SOC2020 occupation codes and employment variables were used to classify registrants as working in roles aligned to their registration, working in non-aligned occupations, or not working. Descriptive analyses examined occupational distributions by profession and country. Results Initial unadjusted findings show that most registrants in both England and Wales were engaged in occupations aligned with clinical practice at the time of the census. However, a minority were working in non-clinical roles or were not in employment. Registrants outside aligned roles were employed across a wide range of occupations, including managerial, educational and administrative roles, with variation by profession and geography. Conclusions Linking NMC register data to Census 2021 demonstrates that registration does not equate to clinical practice. The linked data provide new evidence to inform workforce retention policy.